Depression In Primary Care: Clinical Epidemiology & Clinical Decision Analysis — An Analytical Review - Naqvi, Haider Ali (Journal of Pakistan Psychiatric Society, 2006)
A clinical decision analysis (CDA) is a mathematical tool designed to facilitate complex clinical decisions in which many variables should be considered simultaneously. CDA is a feasible tool for multifaceted problem of management of depression in primary health care. It provides a systematic frame work for organizing all data relevant to the decision on recognition and management of depression. Clinical epidemiological perspective is used for assessing the validity of screening instrument. A decision matrix based on reported probabilities is also constructed. Chance nodes and decisions pertinent to co morbidities, illness severity and treatment options for depression are also presented.